PENGGUNAAN MEDIA FILM ANIMASI UNTUK MENINGKATKAN PENGUASAAN KOSAKATA BAHASA ARAB - Hana, Lifya Nidaul; Sunarko, Asep; Rahman, Rifki Aulia (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2022)
This Study aims to: 1) Determining the use of animated film media in improving Arabic vocabulary mastery; 2) Knowing the increase in mastery of Arabic vocabulary using animated film media; 3) Knowing the difference in mastery of Arabic vocabulary. This study use a quantitative research approach with experimental methods using a pretest-posttest control design. The subject of this research were students of class VII MTs Plus Al Hidayah Kroya, totaling 50 Students who were divided into two classes, namely the experimental class and the control class. The test results were analyzed and compared using the gain test and t test to determine the improvement and differences in arabic vocabulary mastery between the two classes. The result of this study using the t test and again test showed that, the result of hypothesis testing obtained t count of 7, 48, then t count was compared with t table with dk = 25+25-2= 48 and the error level was 5%, so t table = 2,01. From these results, it is obtained that t count is greater than t table (7,48 > 2,01), and the experimental class gain test results are 0,722 and the control class is 0,224. So it can be concluded that students’ Arabic vocabulary mastery using animated film media is better than students who do not use media and there is an increase in students’ Arabic vocabulary mastery using animated film media.